KELAYAKAN FINANSIAL DAN PROSPEK PENGEMBANGAN AGRIBISNIS SENGON (Albazia falcataria) RAKYAT DI KECAMATAN KEMILING KOTA BANDAR LAMPUNG - Dimash Septian Adi Putra; Dyah Aring Hepiana Lestari; M Irfan Affandi (Lampung University, 2015)
This study aims to assess: (1) financial feasibility of sengon agribusiness of people, (2) sensitivity of financial feasibility, (3) prospects for the development of sengon agribusiness of people. This research was conducted in the Kedaung and Sumber Agung village, Kemiling Subdistrict, Bandar Lampung City were selected purposively. Respondents taken a census of 16 people who are farmers of sengon people. The first aim was analyzed using several criteria for measuring investment feasibility. The second aim was analyzed using sensitivity analysis with possibility of decline in production sengon of 11.15%, decrease in selling prices of timber sengon of 17.24%, and increase in production costs by 30%. The third aim assessed by quantitative descriptive and qualitative descriptive analysis. The results showed that: (1) farm sengon is financially feasible to cultivated indicated by the value of NPV Rp97.068.096,99, IRR of 76.96% is greater than the interest rate used is 19.25%, Gross B/C 4.26, Net B/C of 4.81 and PP for 5 years 8 months of age economical business for 6 years, (2) sengon farming is still feasible to decrease production by 11, 15%, decrease in selling prices of timber sengon by 17.24%, and the increase in production costs by 30%, (3) prospects for the development of highly prospective of sengon agribusiness of people or good to be developed. Key words: development prospects, financial, sengon, sensitivity